Empowering minor migrants: peer support program Nantes. (13th November 2019) - Combes, S; Kardiana, D; Le Grand, E; Moreau, D; Quinette, M; Sauzède, S
Abstract: Background: Under-aged migrants (UAMs) may see their legal minority unrecognised by the French state. If they confront this decision at court, they stand in a legal void. They can benefit from a direct access to State Medical Aid and are not submitted to a minimum period of 3 months of staying in France unlike adults. Moreover, when accessing care, unrecognised UAMs are in an unclear situation as they are minors without legal representation. This research is based on a newly created program ran by Doctors of the World (MDM) in Nantes, aiming to enhance UAMs access to health care and rights through peer-support. Peer-support is intended to develop the empowerment the UAM and help them to be able to be the authors of their life thus develop their own abilities (Le Grand, 2018). The role of empowerment in health access is established (Wallerstein, 2006). The research aims at identifying the obstacles and levers in the implementation of the program, the modifications it can cause in the program. Methods: The research is based on 3 months ethnographical observations, 9 formal interviews with UAM, 5 with professionals, and informal interviews. Results: We identify that volunteers share a different perception of what is empowerment. Some would leave quite a large autonomy to UAMs while others find it difficult to alter the organisation to give space to UAMs. Finally, self-help mainly develops abilities of those UAMs who were more resourceful. Conclusions: The analysis shows that a successful program of empowerment rely on shared views of its meaning. Moreover it shows that empowerment may help mainly those resourceful thus exacerbate some inequalities in ressources. Key messages: The notions of empowerment and peer-support need to be well understood by all. Empowerment, as a side effect first exacerbates some inequalities of resources among UAMs.